A communication-based model for describing patients' journeys in hospital accident and emergency departments. Issue 4 (2nd October 2018) - Lam, Marvin
Abstract : A patient's journey refers to the series of events experienced by a patient in the process of receiving care. Most of the existing descriptions presuppose medical knowledge and may not capture a patient's experience because patients are often not well-informed on the medical aspects of care. This paper proposes a communication-based model to describe journeys as series of socio-semiotic activities, which were identified by linguistic analysis of authentic patient–practitioner communication. The model offers new granularity in characterizing the communicative unfolding of journeys, which reflects the participants' roles and informational responsibilities. Practitioners' communicative workload is largely concerned with information rather than actions or procedures, with doctors doing most of the communicative work. This study unpacks the communicative complexity within what would be considered as single steps from the medical point of view with a new sense of length of journeys in terms of communicative load instead of time. The study reported in this paper was conducted in the Cantonese context, which serves as the basis of follow-up studies to correlate patients' experience described with the proposed model and the patients' levels of satisfaction and adherence, and to compare patients' journeys from different parts of the world described by the same model.